Identification of N‐linked glycosylation and putative O‐fucosylation, C‐mannosylation sites in plasma derived ADAMTS13. (May 2014) - Sorvillo, N.; Kaijen, P. H.; Matsumoto, M.; Fujimura, Y.; van der Zwaan, C.; Verbij, F. C.; Pos, W.; Fijnheer, R.; Voorberg, J.; Meijer, A. B.
Summary Background Acquired deficiency of ADAMTS13 causes a rare and life‐threatening disorder called thrombotic thrombocytopenic purpura (TTP). Several studies have shown that aberrant glycosylation can play an important role in the pathogenesis of autoimmune diseases. N‐linked glycosylation and putative O‐fucosylation sites have been predicted or identified in recombinant ADAMTS13. However, it is not known which of these sites are glycosylated in plasma derived ADAMTS13. Objectives Here we investigated the presence of putative O‐fucosylation, C‐mannosylation and N‐linked glycosylation sites on plasma derived ADAMTS13. Methods/Results Sites of N‐linked glycosylation were determined by the use of peptide N‐glycosidase‐F (PNGase F), which removes the entire carbohydrate from the side chain of asparagines. Nine of the 10 predicted N‐linked glycosylation sites were identified in or near the metalloproteinase, spacer, thrombospondin type 1 repeat (TSR1) and the CUB domain of plasma ADAMTS13. Moreover, six putative O‐fucosylated sites were identified in the TSR domains of plasma ADAMTS13 by performing searches of the tandem mass spectrometry (MS/MS) data for loss of hexose (162 Da), deoxyhexose (146 Da), or hexose‐deoxyhexose (308 Da). The use of electron transfer dissociation (ETD) allowed for unambiguous identification of the modified sites. In addition to putative O‐fucosylation and N‐linked glycosylation, two putative C‐mannosylation sites were identified within the TSR1 and TSR4 domains of ADAMTS13. Conclusions Our data identify several glycosylation sites on plasma derived ADAMTS13. We anticipate that our findings may be relevant for the initiation of autoimmune reactivity against ADAMTS13 in patients with acquired TTP.